Burlemarxian Narratives: A Process of International Recognition Through Architecture Exhibitions - Polizzo, Ana Paula (Bitacora Arquitectura, 2020)
The aim of this paper is to discuss the process by which the landscape design of Roberto Burle Marx became known and acknowledged in the hegemonic centers of global culture – the United States and Europe – through architectural exhibitions. For this purpose, it is necessary to understand the different narratives – institutional and curatorial – that molded the foreign vision of his architectural production, which were related to cultural aspirations of both national and international scope.